Adenoid Cystic Carcinoma of the Nasal Cavity and Paranasal Sinuses: A Meta-Analysis - Amit, Moran; Binenbaum, Yoav; Sharma, Kanika; Naomi, Ramer; Ilana, Ramer; Abib, Agbetoba; Miles, Brett; Yang, Xinjie; Lei, Delin; Kristine, Bjoerndal; Christian, Godballe; Thomas, Mücke; Klaus-Dietrich, Wolff; Fliss, Dan; Eckardt, André M.; Chiara, Copelli; Sesenna, Enrico; Frank, Palmer; Patel, Snehal; Gil, Ziv (Journal of Neurological Surgery Part B: Skull Base, 2013)
Objectives To identify independent predictors of outcome in patients with adenoid cystic carcinoma (ACC) of the paranasal sinuses and skull base.Design Meta-analysis of the literature and data from the International ACC Study Group.Setting University-affiliated medical center.Participants The study group consisted of 520 patients, 99 of them from the international cohort. The median follow-up period was 60 months (range, 32 to 100 months).Main Outcome Measures Overall survival (OS) and disease-specific survival (DSS).Results The 5-year OS and DSS of the entire cohort were 62% and 67%, respectively. The local recurrence rate was 36.6%, and the regional recurrence rate was 7%. Distant metastasis, most commonly present in the lung, was recorded in 106 patients (29.1%). In the international cohort, positive margins and ACC of the sphenoid or ethmoidal sinuses were significant predictors of outcome (p < 0.001). Perineural invasion and adjuvant treatment (radiotherapy or chemoradiation) were not associated with prognosis.Conclusion Tumor margin status and tumor site are associated with prognosis in ACC of the paranasal sinuses, whereas perineural invasion is not. Adjuvant treatment apparently has no impact on outcome.
Keywords: adenoid cystic carcinoma; paranasal sinuses; skull base; meta analysis; survival